Reproducing Legal Culture Thru Cultural Capital: A Socio-Legal Analysis of Islamic Higher Education in Indonesia - H. Alhassan, Khalid Ibrahim; Sopian Lubis; Adam Jehan; AB Jalhani; Al Fiqri Ardiansyah (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The crisis of legal culture and the low level of public trust in Indonesia’s legal system suggest that reforms centered on normative and institutional dimensions have failed to address the deeper cultural roots of the problem. One crucial factor that has been relatively overlooked is the role of legal education, particularly Islamic Higher Education, in reproducing or transforming legal cultural orientations. This article examines the patterns, comparative orientation, and socio-legal implications of the legal education curricula at five Islamic higher education institutions, namely UIN Syarif Hidayatullah Jakarta, UIN Sunan Kalijaga Yogyakarta, UIN Maulana Malik Ibrahim Malang, Universitas Muhammadiyah Yogyakarta (UMY), and Universitas Nahdlatul Ulama Indonesia (UNUSIA), during the period 2020–2025. This research uses a socio-legal approach with a comparative method based on an analysis of official curriculum documents, including course structure, credit distribution, graduate learning outcomes, and course plans. The findings indicate the dominance of a normative-formalistic orientation in the legal curriculum, both in the country's positive law and in Islamic jurisprudence. Comparatively, UIN Sunan Kalijaga is relatively the most progressive thru its interdisciplinary-sociolegal approach, followed by UMY with a reformist-social orientation, while UIN Malang emphasizes the ethical-spiritual dimension. Conversely, UIN Jakarta and UNUSIA tend to maintain a formalistic-doctrinal curriculum structure. However, all these innovations are additive and have not yet resulted in a structural repositioning of the core curriculum. Theoretically, this research places Lawrence Friedman's theory of legal culture as the main framework, enriched by Pierre Bourdieu's theory of cultural capital, maqāṣid al-sharīʿah, and Amin Abdullah's integrative-interconnectedness paradigm. This article underscores the need to reposition Islamic legal education curricula so that they are oriented toward substantive justice and the transformation of legal culture.